Examining the Impact of Writing Strategies in Enhancing Pre-Service Teachers’ Mathematical Problem-Solving Skills - Sionicio, Joan Belen (Jurnal Pendidikan Progresif, 2025)
Examining the Impact of Writing Strategies in Enhancing Pre-Service Teachers’ Mathematical Problem-Solving Skills. Objective: This study investigated the impact of structured writing activities in enhancing the pre-service teachers’ mathematical problem-solving skills and examined the challenges they encountered during the implementation of these strategies. Method: A mixed-method research design was employed using problem-solving pretest and posttest and interviews. The study involved 35 second-year pre-service teachers selected from 142 pre-service secondary teachers from a state university in the Philippines through purposive sampling.  Quantitative data were analyzed using descriptive and inferential statistics, while qualiative data obtained from interviews were subjected to thematic analysis. Findings: The results underscored the notable impact of writing strategies in enhancing the pre-service teachers’ problem-solving abilities.  A pretest mean percentage score of 52.29 (developing) increased to 76.86 (proficient) on posttest.  This yielded a moderate normalized gain  of 0.52 and a very large effect size (Cohen’s d = 2.39). The paired t-test showed a significant effect (t = 14.2, p < .001).  The ANCOVA and regression analysis showed that the academic background of the participants did not predict their posttest performance, unlike the pretest.  The qualitative findings revealed the participants’ challenges related to translating their thoughts in writing, limited content knowledge, emotional factors, difficulty in problem comprehension and analysis, and lack of problem-solving strategies. Conclusion: Despite the challenges encountered by the pre-service teachers, the results underscore the positive effect of the structured writing strategies in enhancing their problem-solving skills.   This study suggests that structured writing strategies can be adopted in teacher training curricula to strenghten mathematical reasoning.   It recommends integrating writing strategies in mathematics instruction whether  in the development of the concept or assessment, through reflective writing prompts, logs, or metacognitive writing strategies to enhance students’ problem-solving abilities. Keywords: writing strategies, problem-solving, pre-service teachers, mathematics.